Multicultural acquisitions (Haworth Press, 1993)
This book explores the historical relationship between libraries and minorities and its relationship to the current debate concerning multiculturalism in education. This book also discusses the resources available on several specific individual cultural and subcultural groups. Some of the insightful topics discussed include promoting multicultural learning through children’s literature ; incorporating multicultural literature in suburban public libraries ; the valuable but often-overlooked resource of U.S. government publications on ethnic studies ; building Hispanic collections in public libraries ; a comparative analysis of libraries in historically black colleges and universities ; developing a collection that meets the needs of students doing research in Native American studies ; a bibliography of the most significant books available on the history of women in the United States